The pattern of cardiovascular manifestations in Egyptian Behçet's patients and its relation to disease activity - Nashwa Aly Morshedy; Dalia Fayez Mohammed; Fatma Mohammed Badr; Mohammed Abd El monem Teama (SpringerOpen, 2021)
Abstract Background Behçet's disease (BD) is also referred to as vascular BD when it frequently involves the heart and vessels. This study aimed to describe the cardiovascular manifestations in patients with BD and its correlation to disease activity. We conducted a cross-sectional study on 40 patients diagnosed with BD according to the International Criteria for Behçet's Disease 2014. All the patients were subjected to detailed history taking, full clinical examination, lab investigations, resting electrocardiogram, trans-thoracic echocardiography, and carotid artery duplex for measuring intimal thickness, peripheral arterial and venous duplex, computed tomography pulmonary angiography, and full ophthalmological examination. Regarding the activity of the disease, it was assessed according to the score of Behçet's Disease Current Activity Form (BDCAF). Results The most common cardiac manifestation was valvular lesion (67.5%) where the most frequently affected valve was the tricuspid valve (27.5%). Although 25% of patients had left ventricular diastolic dysfunction, only 5% had intracardiac masses. Approximately 52.5% of patients had vascular lesion (deep venous thrombosis 45%, arterial involvement 7.5% [as pulmonary artery thrombosis 5% and aneurysm 2.5%]). Increase in intima media thickness (IMT) was observed in 7.5% of patients, while 60% had abnormal lipid profiles. Hypercholesterolemia was the most common lipid abnormality (50%). BDCAF score range was 4-12, which was significantly correlated to multiple cardiovascular parameters as a mitral, tricuspid valve, and vascular venous involvement (p < 0.05), while not significantly correlated to lipid profile (p > 0.05). Conclusion Cardiovascular complications are frequent among patients with BD, even those who are asymptomatic; therefore, these complications must be screened for early detection and proper management.